Islamic education leadership model comparative study of K.H. Ahmad Dahlan and K.H. Imam Zarkasy - Sadiah; Abas Mansur Tamam; Hasbi Indra (At Turots: Jurnal Pendidikan Islam, 2026)
This study aims to analyze and compare the leadership models of Islamic education of KH Ahmad Dahlan and KH Imam Zarkasyi in the context of contemporary Islamic education challenges characterized by leadership crises, degradation of values, and demands for adaptation to changing times. This study uses a qualitative approach with a literature study method on various relevant primary and secondary sources. The results of the study show that both figures apply leadership that is transformational, visionary, and oriented towards reforming the people's education system. KH Ahmad Dahlan carried out transformation through the Muhammadiyah movement by emphasizing the integration of religious and general knowledge, reform of learning methods, and strengthening the role of education in building the socio-religious awareness of the community. Meanwhile, KH Imam Zarkasyi modernized the pesantren through institutional system reform, professional education management, an integrated curriculum, and character development of students based on pesantren values. This study concludes that in the midst of the challenges of modernization, globalization, and character crisis, the leadership models of the two figures remain relevant as a strategic reference for the development of sustainable and competitive Islamic education.